Educação ambiental: um relato de experiência na comunidade indígena Assurini, município de Tucuruí/PA - SOUZA, Raiane Contente de (2022)
The research objective is to report the lived experiences in solid waste actions carried out by the Environmental Education Study Group (GEA-CAMTUC), an extension project from Pará’s Federal University, Campus Tucuruí, at the Assurini do Trocará indigenous community in 2019. The study showed that the Environmental Education in non-formal education linked to indigenous environmental knowledges is a fundamental for the impacts mitigation related to health and basic sanitation, which the Assurini people have been subjected during their displacement processes.